Navigate the Sacred-Secular Divide with Reformed Intellectual Patience In Indonesia - Rebekah Earnshaw (Sekolah Tinggi Teologi Bandung, 2024)
The Indonesian Reformed Calvinist theologian must appropriately consider the “sacred-secular divide” (SSD) in order to participate constructively and harmoniously in her context, because despite claims otherwise, practices that separate times and places from divine rule shape her life. She possesses a wealth of resources to enable this from within her theological tradition (Kuyper), from contemporary but non-co-located colleagues (Bailey, Doornbos, McClean, and Webster), and from her immediate social and cultural context (modern pluralistic Indonesia). In light of this, I propose that Christian intellectual patience is a virtue that she can pursue for her to faithfully flourish, because it responds Christianly to both where and when she finds herself. To reach this conclusion we survey the sources and feel the pressure of navigating a night amongst the Indonesian jungle where Wewe Gombel lurks.